2012
DOI: 10.22146/ijc.21363
|View full text |Cite
|
Sign up to set email alerts
|

SECONDARY METABOLITE FROM ENDOPHYTIC FUNGI <i>Aspergillus niger</i> OF THE STEM BARK OF KANDIS GAJAH (<i>Garcinia griffithii</i>)

Abstract: Garcinia griffithii are known as kandis gajah including the Garcinia genus. This plant has been traditionally used by local communities Sarasah

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…These proteins may protect hyphae of saprophytes from chitinases released in root exudates [ 54 ], which are present in the rhizosphere. Moreover, Aspergillus oryzae [ 55 ] and A. niger [ 56 ] can behave as endophytes and, as well as saprophytes. A. niger and Neurospora crassa , well-known saprophytes, can also behave as plant pathogens under certain conditions [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…These proteins may protect hyphae of saprophytes from chitinases released in root exudates [ 54 ], which are present in the rhizosphere. Moreover, Aspergillus oryzae [ 55 ] and A. niger [ 56 ] can behave as endophytes and, as well as saprophytes. A. niger and Neurospora crassa , well-known saprophytes, can also behave as plant pathogens under certain conditions [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were caused by the different nutritional content in each media. PDB is media widely used for fungal growth to produce antibiotics (Margino 2008;Elfita et al 2012). The same situation also happened in the rice washing water used for fungal growth (Thiruvengadam et al 2018).…”
Section: Conidia Density Of Weed Pathogenic Fungi On In-vitro Liquid Mediamentioning
confidence: 97%
“…Results from the detection and identification process showed that Aspergillus niger was the dominant species. This is based on the black colony that grew on the medium (Elfita et al, 2012). Kurniawan et al (2008) reported that Aspergillus niger was one of the fungi isolated from corn seeds.…”
Section: Fungi On Corn Seedsmentioning
confidence: 99%